Types and Classifications of Reduplications in Kelewae Language spoken in Nagekeo District-East Nusa Tenggara and The Implementation in The Classroom - Kita Ngatu, Simon Petrus (Fakultas Keguruan dan Ilmu Pendidikan Universitas Pakuan, 2024)
The present article aims to describe the types of reduplication in Kelewae language spoken in Nagekeo District - East Nusa Tenggara and its implementation in the classroom. The study uses a descriptive qualitative method which describes the types of reduplication in Kelewae language in the form of words, phrases or sentences categorised to be concluded as the result of this writing. Therefore, this type of method is taken as an effective way to fulfil the aim of the study. The informants of this research were selected from 5 native speakers of Kelewae language. The instruments in this research are interviews and translation tasks. In this task, some sentences of types of reduplication were given in Bahasa Indonesia to be translated into Kelewae Language. The aim of the interview is to clarify the data that had been translated into Kelewae Language. The research found that using Kelewae language facilitates students to both understand the elements of reduplication and build the students' awareness of their own culture.